Case Report: Identification of a novel NTRK3-AJUBA fusion co-existing with ETV6-NTRK3 fusion in papillary thyroid carcinoma - Yu, Qing-Xiang; Zhao, Wen-Jun; Wang, He-Yue; Zhang, Lei; Qin, Lan; Zhang, Lei; Han, Jian-li (Frontiers in Oncology, 2023)
NTRK fusions are validated oncogenic drivers of various adult and pediatric tumor types, including thyroid cancer, and serve as a therapeutic target. Recently, tropomyosin receptor kinase (TRK) inhibitors, such as entrectinib and larotrectinib, display promising therapeutic efficacy in NTRK-positive solid tumors. Although some NTRK fusion partners have been identified in thyroid cancer, the spectrum of NTRK fusion is not fully characterized. In this study, a dual NTRK3 fusion was identified by targeted RNA-Seq in a 47-year-old female patient with papillary thyroid carcinoma. The patient harbors a novel in-frame fusion between NTRK3 exon 13 and AJUBA exon 2, co-existing with a known in-frame fusion between ETV6 exon 4 and NTRK3 exon 14. The dual NTRK3 fusion was validated by Sanger sequencing and fluorescence in situ hybridization (FISH) but lack TRK protein expression as defined by pan-TRK immunohistochemistry (IHC). We supposed the pan-TRK IHC result to be falsely negative. In conclusion, we present the first case of a novel NTRK3-AJUBA fusion co-existing with a known ETV6-NTRK3 fusion in thyroid cancer. These findings extend the spectrum of translocation partners in NTRK3 fusion, and the effect of dual NTRK3 fusion on TRK inhibitor therapy and prognosis needs long-term follow-up.